2015
DOI: 10.1021/acs.jafc.5b00832
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Adsorption and in Vivo Pharmacokinetic Interaction between Doxycycline and Frequently Used Mycotoxin Binders in Broiler Chickens

Abstract: Mycotoxin binders are readily mixed in feeds to prevent uptake of mycotoxins by the animal. Concerns were raised for nonspecific binding with orally administered veterinary drugs by the European Food Safety Authority in 2010. This paper describes the screening for in vitro adsorption of doxycycline-a broad-spectrum tetracycline antibiotic-to six different binders that were able to bind >75% of the doxycycline. Next, an in vivo pharmacokinetic interaction study of doxycycline with two of the binders, which demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…Bentonite interacted with tylosin and decreased its passage through IPEC-J2 (Devreese et al 2013). Also, an in vitro study on adsorption of doxycycline by six different adsorbents (four montmorillonite based-clay, sepiolite and leonardite-based binder) showed that less than 25% of the initial concentration of doxycycline was detected after 4 h of incubation at 37°C, suggesting that 75% of doxycycline was adsorbed by mineral adsorbents (De Mil et al 2015). Furthermore, the in vitro results were validated using two of the montmorillonites-based clays, to study the pharmacokinetics and oral bioavailability of doxycycline in vivo.…”
Section: Veterinary Substancesmentioning
confidence: 98%
“…Bentonite interacted with tylosin and decreased its passage through IPEC-J2 (Devreese et al 2013). Also, an in vitro study on adsorption of doxycycline by six different adsorbents (four montmorillonite based-clay, sepiolite and leonardite-based binder) showed that less than 25% of the initial concentration of doxycycline was detected after 4 h of incubation at 37°C, suggesting that 75% of doxycycline was adsorbed by mineral adsorbents (De Mil et al 2015). Furthermore, the in vitro results were validated using two of the montmorillonites-based clays, to study the pharmacokinetics and oral bioavailability of doxycycline in vivo.…”
Section: Veterinary Substancesmentioning
confidence: 98%
“…Common types of mycotoxin binders include calcium montmorillonite clay [5], aluminosilicate clay [6], and yeast cell culture [7]. However, some of these adsorbents may also bind minerals, vitamins, and amino acids in feeds [8], as well as reducing the efficiency of the pharmacokinetics of antibiotics [9]. The use of chemical methods comprising ammoniation, ozonation, and peroxidation in food and feeds is limited as a result of the potential toxicity of chemical residues [10].…”
Section: Introductionmentioning
confidence: 99%
“…Another physical removal strategy is the use of inorganic or organic mycotoxin binders (Ramos et al, 1996 ; Kolosova and Stroka, 2011 ). Although these adsorbing binders have some promising features, some may have adverse nutritional effects due to binding of vitamins and minerals (Huwig et al, 2001 ; Yiannikouris et al, 2006 ) or reducing the efficacy pharmacokinetics of antibiotics (De Mil et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%